Analisa Pertumbuhan Beban Terhadap Ketersediaan Energi Listrik di Sistem Kelistrikan Sulawesi Selatan - Chandra P. Putra; Maickel Tuegeh; Hans Tumaliang; Lily S. Patras (Universitas Sam Ratulangi, 2014)
Abstrack– In the electrical system the forecast strategy on load growth and power supply is needed , since the need of the electrical energy will growth continuously each year. The population growth and economic factors of a region are believed to be the triggering factors to increasing consumption of electrical energy in the area. These conditions must be anticipated as early as possible so that the availability of electrical energy can be provided in sufficient quantity. This final project aims to scheme the number of customer electrical energy, electrical energy needs, the production of electric energy and peak load, in South Sulawesi 2013 to 2017 by using the software LEAP (Long-range Energy Alternatives Planning System). Furthermore, determine the schedule when supplementary generation capacity of electric energy supply shortage based on the projected results, and examine potential sources of primary energy in South Sulawesi. The results of the schemed amount of electricity customers in South Sulawesi is constantly increasing from 2013 - 2017, with average growth is 6.12 percent per year, the increasing of customer is 1,566,389.75 in 2013 to 1,986,773.15 in 2017, the average consumption growth of electrical energy during the period by 12.95 percent per year, with a total consumption in 2017 amounted to 6,513,880.42 MWh. Projected production of electric energy is also increased according to the increase in electrical energy consumption with average growth 13.1 percent per year or a total of 7,336,253.33 MWh in 2017. Results of peak load growth projected average is 12.98 percent per year, the total electric energy needs in 2017 amounted to 1,323.02 MW. Based on a projection of the electrical energy needs in South Sulawesi for 2013 - 2017, to be able to fulfill electrical energy needs in 2017, the planned generator capacity expansion scheduled to be done gradually from 2014 to 2016, with the plan to increase generating capacity to 330 MW. South Sulawesi has a lot of potential primary energy that can be used as an alternative power plant development, including: water energy that can be harnessed into reach 1,835.8 MW hydro and micro power of 68.84 MW, natural gas reserves amounted to 377.3 BSCF measured, measured reserves of coal with 5.2 million tons and geothermal capacity reaches 1,950 MW. Key words : Electrical energy, Electrical energy needs, LEAP, The availability of electrical energy, Potential primary energy Abstrak– Dalam sistem kelistrikan strategi perkiraan pertumbuhan beban dan penyediaan daya sangat dibutuhkan, dikarenakan kebutuhan masyarakat akan energi listrik terus bertumbuh setiap tahunnya. Disamping pertumbuhan penduduk, faktor ekonomi suatu daerah juga diyakini sebagai salah satu faktor pemicu meningkatnya konsumsi energi listrik di daerah tersebut. Kondisi ini tentunya harus diantisipasi sedini mungkin agar ketersediaan energi listrik dapat tersedia dalam jumlah yang cukup. Tugas akhir ini bertujuan untuk memproyeksikan jumlah pelanggan energi listrik, kebutuhan energi listrik, produksi energi listrik dan beban puncak, di Sulawesi Selatan tahun 2013 sampai tahun 2017 menggunakan perangkat lunak LEAP (Long-range Energy Alternatives Planning System). Selain itu, akan ditentukan jadwal penambahan kapasitas pembangkit bila terjadi kekurangan pasokan energi listrik sesuai dengan hasil proyeksi, serta mengkaji potensi sumber energi primer yang ada di Sulawesi Selatan. Hasil proyeksi jumlah pelanggan energi listrik di Sulawesi Selatan terus mengalami peningkatan dari tahun 2013 – 2017 , dengan pertumbuhan rata – rata sebesar 6.12 persen per tahun atau meningkat dari 1,566,389.75 pelanggan pada tahun 2013 menjadi 1,986,773.15 pelanggan pada tahun 2017, pertumbuhan rata – rata konsumsi energi listrik selama periode tersebut sebesar 12.95 persen per tahun dengan total konsumsi pada tahun 2017 sebesar 6,513,880.42 MWh. Proyeksi produksi energi listrik juga meningkat sesuai dengan peningkatan konsumsi energi listrik dengan pertumbuhan rata – rata 13.1 persen per tahun atau sebesar 7,336,253.33 MWh pada tahun 2017. Hasil proyeksi beban puncak bertumbuh rata – rata 12.98 persen per tahun, dengan total kebutuhan energi listrik pada tahun 2017 sebesar 1,323.02 MW. Berdasarkan hasil proyeksi kebutuhan energi listrik Sulawesi Selatan tahun 2013 – 2017, untuk dapat memenuhi kebutuhan energi listrik sampai tahun 2017, maka direncanakan penambahan kapasitas pembangkit dijadwalkan dilakukan secara bertahap dari tahun 2014 sampai tahun 2016, dengan rencana penambahan kapasitas pembangkit sebesar 330 MW. Provinsi Sulawesi Selatan memiliki banyak potensi energi primer yang dapat dimanfaatkan sebagai alternatif pengembangan pembangkit listrik, diantaranya: energi air yang dapat dimanfaatkan menjadi PLTA mencapai 1,835.8 MW dan PLTM sebesar 68.84 MW, gas alam dengan cadangan terukur sebesar 377.3 BSCF, batu bara dengan cadangan terukur 5.2 juta ton dan panas bumi dengan kapasitas mencapai 1,950 MW. Kata Kunci : Energi listrik, Kebutuhan energi listrik, Ketersediaan energi listrik, LEAP, Potensi energi primer